Motivational practices as correlates of teachers' task performance in Oyo state (2009)
The study investigated the patterns of motivational practices utilized to induce teachers to work and the extent to which these motivational practices explain teachers' task performance in Oyo state. The ex-post-facto type of research was adopted, in which eighty teachers were randomly selected and rated by eight hundred students from fourty senior secondary schools in eight local government areas of Oyo state. Two instruments, Teachers' Motivational Descriptive Questionnaire (T. M. D. Q) and Task Performance Rating Scale (T. P. R. S) were used to gather information from the teachers and the students. The set of data obtained from the study were analysed using descriptive statistics and multiple regression analysis. Study results show that the level of motivational practices utilised by the government to induce teachers to work in Oyo state are high in salaries; modest in job security and opportunity for promotion while those utilized by the school were preceived to be significantly low in the way teachers' work are supervised, but modest in the amount of freedom to determine studetns' progress. Also, the twenty motivational practices significantly explained the variance in teachers' task performance with a multiple regression R of 0.93, accounting for 87.2% of variance in teachers' task performance. Four motivational practices utilised respectively by the government and school yielded significant relative contributions to task performance. These findings have implications for policy makers, government, school personnel in administrative capacities (principals) and others who are in the position to manage teachers' welfare.